“B. A. C. H. - MISSAL FOR ORGAN”, BY EDUARD TERÉNYI - Anamaria Mădălina HOTORAN (Studia Universitatis Babeş-Bolyai. Musica)
B. A. C. H. missal for the organ op. 4 (1967) constitutes the prototype of the creation period of the 62s – 72s that is considered by the maestro Eduard Terényi to be “constructivist” or “the crystal music”, that is characterized through symmetry (melodic lines, chords, mirrored rhythmic reports) and also, the closeness to the serialisation through the application of certain pre-established rhythmical-melodically patterns.